Pengaruh Model Pembelajaran SQ3R terhadap Kemampuan Menulis Resensi Kelas XI MAS PPQ Al Washliyah Firdaus Tahun Pelajaran 2023/2024 - Juliana, Eva; Harahap, Andi Syahputra; Zahra, Siti Fatimah (Universitas Islam Sumatera Utara, 2025)
Writing review skills are essential competencies for students, particularly in fostering critical thinking and effective communication. This study aims to assess the impact of the SQ3R (Survey, Question, Read, Recite, Review) learning model on enhancing the review writing skills of eleventh-grade students at MA Swasta PPQ Al Washliyah Firdaus during the 2023/2024 academic year. The research focuses on the implementation of the SQ3R method and its effectiveness in improving writing skills. Employing a pre-experimental method with a one-group pretest-posttest design and a quantitative approach, this study involved 52 students as research subjects. Data were collected through observation, questionnaires, and pretest-posttest writing assessments. The results demonstrate a significant improvement in students' writing performance after the implementation of the SQ3R model, with a posttest average score of 80.4 compared to a pretest average score of 74 using conventional methods. These findings suggest that the structured steps of the SQ3R model effectively support students in comprehending texts and producing well-organized reviews, thereby contributing to the development of their academic writing abilities.